Development And Characterization Of A Small-Scale Self-Sustained Steam-Biomass Gasifier - Prbagaran, Sritharan (Universiti Sains Malaysia, 2021)
The world is evolving toward renewable energy due to an increase in energy consumption and environmental concerns. Biomass represents a growing potential source of renewable energy. Thermochemical and biological conversions are the two most common methods for converting biomass to energy. Gasification is a thermochemical process that typically involves converting solid fuel into gaseous fuel known as producer gas (PG) by using a gasifying agent. The utilisation of air as a gasifying agent will produce a low quality producer gas (PG) with low hydrogen production. Steam will be used as a gasifying agent to overcome this issue because steam can enrich hydrogen production. A self-sustained steam biomass gasifier was built which includes self-heating supply from the burning part of the producer gas. Thus, the use of steam as gasification agents was explored in this research. Steam was generated using an electric steam boiler. The gasifier performance and gasification processes were characterised based on several parameters such as gasifier outlet temperature, gasifier grate temperature, steam flow rate, steam-to-biomass ratio, biomass consumption, and producer gas composition. The steam to biomass ratio used in this experiment was in the range of 2.82 to 9.92. As for the gasifier characterisation, the highest temperature recorded at the grate was 369 ºC at a steam flow rate of 21.88 g/min. 21.88 g/min of steam flow rate gave the highest temperature at the grate for steam gasification, and the biomass flow rate was high at 52.78 g/min flow rate. The highest H2 production achieved was at S/B ratio of 4.81, with HHV of PG obtained was 4.68 MJ/Nm3.